Component deployment using parallel ant-nests. (1st January 2011) - Csorba, Máté J.; Heegaard, Poul E.; Herrmann, Peter
This paper targets the problem of efficient software component deployment in distributed networked services. We approach the problem from a model-based service development aspect and propose a solution based on novel methods applied in network management. The swarm intelligence-based deployment logic we have developed uses service models that are defined in UML 2.0. These service models are embellished to contain the non-functional requirements against the implementation of the service that are necessary to solve the component deployment problem and to obtain a deployment mapping. The result of the heuristic optimisation procedure is mappings between the components and the resources provided by the execution environment the service is deployed into. In this work, the deployment is viewed from the perspective of the service provider and our algorithm possesses significant potential in providing adaptation support for services in various changing environments.